2015
DOI: 10.2147/jaa.s80245
|View full text |Cite
|
Sign up to set email alerts
|

The impact of parental history on children's risk of asthma: a study based on the National Health and Nutrition Examination Survey-III

Abstract: PurposeThis study aimed to examine the separate effects of maternal and paternal history on the onset of asthma in children and evaluate the relationship between age of asthma onset in parents and risk of asthma in their children.MethodsWe used data from the third National Health and Nutrition Examination Survey. We developed new continuous standardized scores for survey data to quantify parental history that incorporated both the occurrence of asthma and the age at onset, and associated these scores with asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“… 12 Xu et al revealed that maternal history of asthma (HR: 3.71) was strongly associated with offspring asthma. 31 In our study, children born to a parent with a history of asthma was significantly associated with childhood asthma. However, Delbley et al found that CS births are associated with subsequent asthma hospitalisation only in premature and mothers with asthma have increased rates of CS and premature delivery.…”
Section: Discussionmentioning
confidence: 47%
“… 12 Xu et al revealed that maternal history of asthma (HR: 3.71) was strongly associated with offspring asthma. 31 In our study, children born to a parent with a history of asthma was significantly associated with childhood asthma. However, Delbley et al found that CS births are associated with subsequent asthma hospitalisation only in premature and mothers with asthma have increased rates of CS and premature delivery.…”
Section: Discussionmentioning
confidence: 47%
“…The majority of studies (28 out of 31) investigated the relationship between antibiotic exposure and asthma development, while only seven studies considered the food or non-food allergies and nine examined the development of eczema. All studies reported risk estimates and adjusted risk estimates, but although the investigated confounding factors differed, all studies included maternal history factors, which is known to be important [ 102 ]. The quality of studies ranged from 7 to 9 on the NOS scale (average 7.9), suggesting overall high methodological quality ( Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A family history of allergy, especially maternal allergy, is associated with an increased likelihood of allergic sensitization and allergic diseases during childhood. 1, 2 Furthermore, infancy and early childhood may be a critical period for environmental exposures to modulate allergic disease risk. While breastfeeding and delivery mode appear to modify risk of childhood allergic outcomes, 35 it is unclear if they have the potential to attenuate or intensify the risk associated with vertical transmission of maternal atopy.…”
mentioning
confidence: 99%